Comparative Analysis of Cost and Durability of Sch 40 Galvanized Pipe and Sch 80 Black Pipe for Seachest Sea Water Systems KM. Pratiwi Indah - Mursidi, Mursidi; Awwalin, Rodlitul; Zunaeda, Wingky Okta (Universitas Hang Tuah, 2026)
The seawater piping system on KM. Pratiwi Indah plays an important role in supporting ship operations; however, it is highly susceptible to damage due to the corrosive marine environment. This study aims to identify the causes of the seawater piping system replacement, compare the costs between galvanized pipe SCH 40 and black pipe SCH 80, and analyze the corrosion resistance of both pipe types. The research methods include the calculation of corrosion rate, remaining life, and Life Cycle Cost (LCC), supported by data presentation in tables and graphs. The analysis results indicate that the galvanized pipe has a corrosion rate of 0.35 mm/year with a remaining life of 15.14 years, while the black pipe has a corrosion rate of 0.53 mm/year with a remaining life of 16.41 years. Although the black pipe shows a slightly longer remaining life, the LCC calculation over a 30-year analysis period demonstrates that the galvanized pipe results in a lower total life cycle cost. Based on the technical and economic analysis, the galvanized SCH 40 pipe is recommended as the more optimal material for the seawater piping system on KM. Pratiwi Indah.